2011
DOI: 10.1007/s11689-011-9074-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeted treatments for fragile X syndrome

Abstract: Fragile X syndrome (FXS) is the most common identifiable genetic cause of intellectual disability and autistic spectrum disorders (ASD), with up to 50% of males and some females with FXS meeting criteria for ASD. Autistic features are present in a very high percent of individuals with FXS, even those who do not meet full criteria for ASD. Recent major advances have been made in the understanding of the neurobiology and functions of FMRP, the FMR1 (fragile X mental retardation 1) gene product, which is absent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 135 publications
(213 reference statements)
1
89
0
Order By: Relevance
“…A previous study by Jennings et al demonstrated that GABAergic (Vgat-expressing) neurons in the LH are responsible for producing appetitive and consummatory behaviors (14). FXS animal models have lowered GABA subunit receptors, synthesis of GABA, GABAergic input to many regions of the brain, and increased catabolism of GABA (15,16). Similarly, cerebral GABAA receptor expression is reduced in several brain regions of subjects with PWS (17).…”
Section: Neurobiology Of Fxs With Pwpmentioning
confidence: 99%
“…A previous study by Jennings et al demonstrated that GABAergic (Vgat-expressing) neurons in the LH are responsible for producing appetitive and consummatory behaviors (14). FXS animal models have lowered GABA subunit receptors, synthesis of GABA, GABAergic input to many regions of the brain, and increased catabolism of GABA (15,16). Similarly, cerebral GABAA receptor expression is reduced in several brain regions of subjects with PWS (17).…”
Section: Neurobiology Of Fxs With Pwpmentioning
confidence: 99%
“…Previous studies recruiting from programs focused on epilepsy and neurology clinics reported a broad range of 14% to 44% prevalence, [30][31][32][33][34][35][36][37][38] and genetics clinics reported an intermediate range of 9% to 27%. [39][40][41][42] Larger studies focused on people with FXS in the community or FXS clinics reported lower prevalence rates overall, ranging from 12% to 18%, 29,[43][44][45] and with higher prevalence for male than for female patients. In the FXCRC Database, seizures had occurred in 10% of patients, with a higher prevalence in male patients than in female patients (Table 1).…”
Section: Neurologic Disordersmentioning
confidence: 99%
“…48,49 Seizures are easily controlled 29,31,36,38,42,45,47 and resolve during childhood in the majority of people with FXS. 43,47 Routine EEG screening of people with FXS is not recommended unless the patient presents with behaviors or episodes that might represent seizures.…”
Section: Neurologic Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes known to be causes of ASD interact with the translational *Corresponding author: Nagwa A Meguid, Professor of Human Genetics, National Research Centre, Cairo, Egypt, E-mail: meguidna@yahoo.com pathway defective in FXS, and it has been hypothesized that there will be substantial overlap in molecular pathways and mechanisms of synaptic dysfunction between FXS and ASD [13]. It was suggested that the difference between the 2 groups in the medial prefrontal and anterior cingulated cortices thickness may entail an altered social cognitive style [14].…”
mentioning
confidence: 99%